The Importance of Internal Control and its Contribution to Property Asset Management - Requena Torres, Daniel Oscar (2023)
This research paper emphasizes the importance of implementing internal control in public entities, particularly in the Superintendencia Nacional de Aduanas y de Administración Tributaria (SUNAT), to enhance the efficiency of property asset management. The main aim of this paper is to create awareness among public servants about the benefits and implications of introducing an internal control system in the entity, and to understand its correlation with institutional processes. The study employed a quantitative, descriptive, correlational, and explanatory methodology, with a non-experimental design. The independent variable, internal control policies, and the dependent variable, efficient management of property assets, were defined using various publications related to the topic. The data collection technique used was a survey, administered to a sample of 50 professionals, including officials and civil servants responsible for property asset management. The study also included a review of the information provided by SUNAT to ensure coherence in the results.